A Strategic Roadmap to Sustainability in the Fashion Industry: Creating Business Models that Deliver Long-Term Societal Impact and Value Creation (MSW Management Journal, 2026)
The global fashion industry faces mounting pressure to reconcile commercial imperatives with escalating environmental and social challenges. This study develops and empirically tests a strategic sustainability roadmap by examining four theoretically grounded pathways: the influence of sustainable business practices on long-term value creation; the impact of circular economy strategies on environmental sustainability performance; the role of corporate social responsibility (CSR) initiatives in generating societal impact; and the contribution of sustainable innovation to competitive advantage. Using a quantitative, survey-based design administered to 400 fashion industry professionals across firm sizes and sectors, multiple linear regression analysis (IBM SPSS v25) was employed to test four hypotheses. All models yielded high explanatory power (R² = .662 to .719) with strong model fit (F = 154 to 202, p < .001). Cronbach's alpha values ranged from 0.843 to 0.858, confirming robust scale reliability. Findings reveal that top management commitment (β = 0.267), digital sustainability integration (β = 0.298), CSR transparency (β = 0.247), and sustainable material sourcing (β = 0.286) are the dominant drivers of their respective outcomes. The paper contributes a multi-dimensional empirical roadmap for sustainable fashion strategy and offers practical implications for managers, policymakers, and investors.